Servant first : a multicase study exploring servant leadership in community college instructional administrators - Elliott, Marvin Lee (2012)
The purpose of this study was to explore the application of servant leadership principles to community college instructional administration. The study conducted was a multicase research design. The conceptual framework for the study was based on Greenleaf’s work in servant leadership as expressed in 10 characteristics of servant leaders defined by Spears: listening, empathy, healing, awareness, persuasion, conceptualization, foresight, stewardship, commitment to the growth of people, and building community. Three community college chief academic officers were selected through a nomination process. Chief academic officer participants were selected because they were identified by their presidents and peers as displaying characteristics that appeared to be consistent with servant leadership. The three chief academic officers participated in semi-structured, one-on-one interviews, observation, and document analysis. In addition, five or six direct reports of each chief academic officer participated in semi-structured, one-on-one interviews regarding their supervisor’s leadership. The major findings of the study affirmed that all three chief academic officers displayed all 10 characteristics of a servant leader identified by Spears, with three of those characteristics being identified more frequently than the others and one characteristic being identified less frequently than the others. The varied strengths were reflective of the chief academic officers’ diverse backgrounds, interests, and passions. Characteristics displayed by the three chief academic officers in addition to the 10 characteristics identified by Spears included honesty, courage, commitment to family, dedication, flexibility, and informality. The study also revealed that the direct reports attributed many positive experiences to their supervisor’s leadership philosophy and behaviors. One criticism was the amount of time consumed by the collaborative effort that is a hallmark of the three CAOs’ leadership. The study concluded that there are servant leaders who occupy positions as community college chief academic officers. It was further concluded that those who report to servant leaders who occupy positions as community college chief academic officers have very positive and satisfying work experiences that largely stem from their supervisor’s leadership style. The study concluded with recommendations for community college administrators, servant leaders, and future researchers.